2022
DOI: 10.2147/amep.s348062
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Mindfulness Meditation on Trait Mindfulness, Perceived Stress, Cortisol, and C-Reactive Protein in Nursing Students: A Randomized Controlled Trial

Abstract: Purpose: Mindfulness meditation was used to reduce stress and its responses such as cortisol and C-reactive protein (CRP) among healthy and ill individuals in various cultures, but its effect has not yet been studied among nursing students, experiencing tremendous stress. The objective of this study was to examine the effects of mindfulness meditation on trait mindfulness, perceived stress, serum cortisol, and serum C-reactive proteins (CRP) in nursing students. Patients and Methods: Using a two-arm, randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 42 publications
2
11
0
5
Order By: Relevance
“…This supports the notion that mindfulness meditation practice encompasses and fosters trait mindfulness (Alhawatmeh et al, 2022;Himichi et al, 2021;Karl & Fischer, 2022;Kiken et al, 2015;Thiermann & Sheate, 2022), involving sustained attention to one's ongoing sensory, cognitive, and emotional experience, without giving in to the natural tendency to react, elaborate, or evaluate (Bishop et al, 2004;Keng et al, 2011;Papies et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…This supports the notion that mindfulness meditation practice encompasses and fosters trait mindfulness (Alhawatmeh et al, 2022;Himichi et al, 2021;Karl & Fischer, 2022;Kiken et al, 2015;Thiermann & Sheate, 2022), involving sustained attention to one's ongoing sensory, cognitive, and emotional experience, without giving in to the natural tendency to react, elaborate, or evaluate (Bishop et al, 2004;Keng et al, 2011;Papies et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…According to a previous study, university students with low resilience showed higher scores in perceived stress [49]. Furthermore, mindfulness meditation was significantly effective in decreasing serum cortisol levels and perceived stress [50]. Therefore, providing programs focused on resilience and mindfulness meditation could be beneficial for students, particularly those who experience high stress.…”
Section: Discussionmentioning
confidence: 96%
“…An 8-week mindfulness training program led to decreased morning cortisol levels and improved self-reported sleep for individuals considered novices at mindfulness training [82]. Moreover, a randomized controlled study of nursing students demonstrated decreased serum cortisol levels and perceived stress after receiving five mindfulness training sessions compared with a control group that just sat quietly [83]. DHEA secretion may moderate stress by offsetting the effects of cortisol.…”
Section: Mindfulness and Physiological Components Of Resiliencementioning
confidence: 98%